Metal hydride thermal heat storage prototype for concentrating solar thermal power - Paskevicius, M.; Sheppard, Drew; Williamson, K.; Buckley, Craig (Elsevier Ltd, 2015)
CSP (concentrating solar thermal power) is emerging as a viable and cost effective solution to renewable energy generation. Molten salts are currently used as heat storage media to enable power generation during the night-cycle. Metal hydrides offer the possibility of storing energy with an order of magnitude less raw material than molten salts due to their impressive energy densities. To test the viability of hydrogen storage materials for CSP applications we have designed and constructed a prototype scale apparatus for screening materials under dynamic conditions with active heat extraction. The apparatus is tested with 19 g of well-known MgH2 to assess the viability of the design for screening purposes. The metal hydride is thermally cycled up to 420 °C more than 20 times with a minimal loss in hydrogen capacity. Issues relating to testing on a prototype scale are discussed, where problems with environmental heat loss and powder compaction dominate the performance of the metal hydride in the prototype. Problems with heat loss are inherently minimised on scale-up, leading to thermal behaviour more representative of a full-scale CSP energy storage system.